23Na MRI Depicts Early Changes in Ion Homeostasis in Skeletal Muscle Tissue of Patients With Duchenne Muscular Dystrophy - Gerhalter, Teresa; Gast, Lena; Marty, Benjamin; Martin, Jan; Trollmann, Regina; Schüssler, Stephanie; Roemer, Frank; Uder, Michael; Schröder, Rolf; Carlier, Pierre G.; Nagel, Armin Michael; Laun, Frederik Bernd (Journal of Magnetic Resonance Imaging, 2019)
BACKGROUND: Duchenne muscular dystrophy (DMD) is a hereditary neuromuscular disease leading to progressive muscle wasting. Since there is a need for MRI variables that serve as early sensitive indicators of response to treatment, several quantitative MRI methods have been suggested for disease monitoring. PURPOSE: To evaluate the potential of sodium (23 Na) and proton (1 H) MRI methods to assess early pathological changes in skeletal muscle of DMD. STUDY TYPE: Prospective clinical study. POPULATION: 23 Na and 1 H MRI of the right leg were performed in 13 patients with DMD (age 7.8 ± 2.4) and 14 healthy boys (age 9.5 ± 2.2). FIELD STRENGTH/SEQUENCE: 3 T including a multiecho-spin-echo sequence, diffusion-weighted sequences, 1 H spectroscopy, 3-pt Dixon, and 23 Na ultrashort echo time sequences. ASSESSMENT: We obtained water T2 maps, fat fraction (FF), pH, and diffusion properties of the skeletal muscle tissue. Moreover, total tissue sodium concentration (TSC) was calculated from the 23 Na sequence. Intracellular-weighted 23 Na signal (ICwS) was derived from 23 Na inversion-recovery imaging. STATISTICAL TESTS: Results from DMD patients and controls were compared using Wilcoxon rank-sum tests and repeated analysis of variance (ANOVA). Spearman-rank correlations and area under the curve (AUC) were calculated to assess the performance of the different MRI methods to distinguish dystrophic from healthy muscle tissue. RESULTS: FF, water T2 , and pH were higher in DMD patients (0.07 ± 0.03, 39.4 ± 0.8 msec, 7.06 ± 0.03, all P < 0.05) than in controls (0.02 ± 0.01, 36.0 ± 0.4 msec, 7.03 ± 0.02). No difference was observed in diffusion properties. TSC (26.0 ± 1.3 mM, P < 0.05) and ICwS (0.69 ± 0.05 a.u., P < 0.05) were elevated in DMD (controls: 16.5 ± 1.3 mM and 0.47 ± 0.04 a.u.). The ICwS was frequently abnormal in DMD even when water T2 , FF, and pH were in the normal range. 23 Na MRI showed higher AUC values in comparison to the 1 H methods. DATA CONCLUSION: Sodium anomalies were regularly observed in patients with DMD compared with controls, and were present even in absence of fatty degenerative changes and water T2 increases. LEVEL OF EVIDENCE: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2019;50:1103-1113.
CRIS-Team Scopus Importer:2019-09-20
Keywords: Duchenne muscular dystrophy; proton MRI; skeletal muscle; sodium MRI

246th ENMC International Workshop: Protein aggregate myopathies 24–26 May 2019, Hoofddorp, The Netherlands - Olivé, Montse; Winter, Lilli; Fürst, Dieter O.; Schröder, Rolf (Neuromuscular Disorders, 2020)
CRIS-Team Scopus Importer:2020-12-25

AAV-mediated cardiac gene transfer of wild-type desmin in mouse models for recessive desminopathies - Ruppert, T.; Heckmann, M. B.; Rapti, K.; Schultheis, D.; Jungmann, A.; Katus, H. A.; Winter, Lilli; Frey, N.; Clemen, C. S.; Schröder, Rolf; Müller, O. J. (Gene Therapy, 2020)
Mutations in the human desmin gene cause autosomal-dominant and recessive cardiomyopathies and myopathies with marked phenotypic variability. Here, we investigated the effects of adeno-associated virus (AAV)-mediated cardiac wild-type desmin expression in homozygous desmin knockout (DKO) and homozygous R349P desmin knockin (DKI) mice. These mice serve as disease models for two subforms of autosomal-recessive desminopathies, the former for the one with a complete lack of desmin protein and the latter for the one with solely mutant desmin protein expression in conjunction with protein aggregation pathology in striated muscle. Two-month-old mice were injected with either a single dose of 5 × 1012 AAV9-hTNT2-mDes (AAV-Des) vector genomes or NaCl as control. One week after injection, mice were subjected to a forced swimming exercise protocol for 4 weeks. Cardiac function was monitored over a period of 15 month after injection and before the mice were sacrificed for biochemical and morphological analysis. AAV-mediated cardiac expression of wild-type desmin in both the homozygous DKO and DKI backgrounds reached levels seen in wild-type mice. Notably, AAV-Des treated DKO mice showed a regular subcellular distribution of desmin as well as a normalization of functional and morphological cardiac parameters. Treated DKI mice, however, showed an aberrant subcellular localization of desmin, unchanged functional cardiac parameters, and a trend toward an increased cardiac fibrosis. In conclusion, the effect of a high-dose AAV9-based desmin gene therapy is highly beneficial for the heart in DKO animals, but not in DKI mice.
CRIS-Team Scopus Importer:2020-05-02

Advanced Fiber Type-Specific Protein Profiles Derived from Adult Murine Skeletal Muscle - Eggers, Britta; Schork, Karin; Turewicz, Michael; Barkovits, Katalin; Eisenacher, Martin; Schröder, Rolf; Clemen, Christoph S.; Marcus, Katrin (Proteomes, 2021)
Skeletal muscle is a heterogeneous tissue consisting of blood vessels, connective tissue, and muscle fibers. The last are highly adaptive and can change their molecular composition depending on external and internal factors, such as exercise, age, and disease. Thus, examination of the skeletal muscles at the fiber type level is essential to detect potential alterations. Therefore, we established a protocol in which myosin heavy chain isoform immunolabeled muscle fibers were laser microdissected and separately investigated by mass spectrometry to develop advanced proteomic profiles of all murine skeletal muscle fiber types. All data are available via ProteomeXchange with the identifier PXD025359. Our in-depth mass spectrometric analysis revealed unique fiber type protein profiles, confirming fiber type-specific metabolic properties and revealing a more versatile function of type IIx fibers. Furthermore, we found that multiple myopathy-associated proteins were enriched in type I and IIa fibers. To further optimize the assignment of fiber types based on the protein profile, we developed a hypothesis-free machine-learning approach, identified a discriminative peptide panel, and confirmed our panel using a public data set.
CRIS-Team WoS Importer:2021-07-09

Aging-related progressive skeletal muscle weakness in mutant DesR349P muscles: a matter of compromised cytoarchitecture - Diermeier, Stefanie; Buttgereit, Andreas; Clemen, CS; Schröder, Rolf; Friedrich, Oliver (Acta Physiologica, 2016)

C9ORF72-ALS: P62- and ubiquitin-aggregation pathology in skeletal muscle - Türk, Matthias; Haaker, Gerrit; Winter, Lilli; Just, Walter; Nickel, Franziska; Linker, Ralf; Chevessier, Frederic; Schröder, Rolf (Muscle & Nerve, 2014)
EVALuna2:7243

Camptocormia as the presenting symptom in sporadic late onset nemaline myopathy: A case report - Türk, Matthias; Nagel, Armin Michael; Roemer, Frank; Schlötzer-Schrehardt, Ursula; Thiel, Christian; Winterholler, Martin; Schröder, Rolf (BMC Musculoskeletal Disorders, 2019)
Background: Camptocormia has been reported in a plethora of diseases comprising disorders of the central nervous system, the peripheral nervous system, and the neuromuscular junction as well as hereditary and acquired myopathies. In sporadic late onset nemaline myopathy concomitant axial myopathy is common, but reports about camptocormia as the only presenting symptom in this condition are very rare. Notably, sporadic late onset nemaline myopathy is a potentially treatable condition in particular when associated with monoclonal gammopathy of unknown significance, HIV or rheumatological disorders. Case presentation: We report the case of a 62-year-old female patient, who presented with slowly progressive camptocormia. Comprehensive work-up including neurological work-up, laboratory tests, MR-imaging, muscle biopsy and genetic testing led to the diagnosis of sporadic late onset nemaline myopathy. Conclusions: Our case report highlights that sporadic late onset nemaline myopathy has to be considered in patients presenting with isolated camptocormia and comprehensive work-up of camptocormia is mandatory to ascertain the individual diagnosis, especially in consideration of treatable conditions.
CRIS-Team Scopus Importer:2019-12-03
Keywords: Axial myopathy; Camptocormia; Muscle biopsy; Nemaline rods; SLONM; Sporadic late onset nemaline myopathy

Cardiomyopathy in Duchenne Muscular Dystrophy: Current Value of Clinical, Electrophysiological and Imaging Findings in Children and Teenagers - Dittrich, Sven; Türk, Matthias; Haaker, G.; Greim, V.; Buchholz, A.; Burkhardt, B.; Fujak, A.; Trollmann, Regina; Schmid, Andrea; Schröder, Rolf (Klinische Pädiatrie, 2015)
Progressive cardiomyopathy (CMP) is one main cause of death in DMD. This cross-sectional assessment of different cardiac diagnostic procedures focusses on preterm diagnosis of cardiac dysfunction.39 male DMD patients aged 6-20 years were included. 6 patients were still ambulatory, 21 patients received corticosteroid therapy.All patients were investigated by ECG, Holter ECG and heart rate variability (HRV), B-type natriuretic peptide (BNP), echocardiography (TTE), tissue Doppler Imaging (TD) and magnetic resonance imaging (MRI) with Late Gadolinium enhancement (LE) and segmental wall motion analysis (WMA).56% of the patients showed repolarization abnormalities and 76% altered HRV. Subnormal ventricular function was found in 25% by TTE and in 34% by MRI. TD differed from normal controls only in the apical septum. In MRI 89% of the patients showed different distribution and intensity of LE and WM restriction. The extent of LE was less in patients after steroid treatment (p<0.05).MRI with segmental LE- and WM-analysis seems to be superior to TTE and TD in exploring regional distribution and severity of damage of the myocardium. ECG and HRV abnormalities are common in DMD-patients but not tightly predictive for segmental and global left ventricular dysfunction. Targeted treatment of CMP in DMD needs prospective evaluation.A timely cardiac MRI is the most sensitive investigation for the identification of early myocardial changes in DMD which is a prerequisite for early interventions and therapeutic strategies.
EVALuna2:7289

CD19-targeted CAR T cells in refractory antisynthetase syndrome - Müller, Fabian; Böltz, Sebastian; Knitza, Johannes; Aigner, Michael; Völkl, Simon; Kharboutli, Soraya; Reimann, Hannah; Taubmann, Jule; Kretschmann, Sascha; Rösler, Wolf; Manger, Bernhard; Wacker, Jochen; et al. (Lancet, 2023)
CRIS-Team Scopus Importer:2023-03-24

Chemical chaperone ameliorates pathological protein aggregation in plectin-deficient muscle - Winter, Lilli; Staszewska, Ilona; Mihailovska, Eva; Fischer, Irmgard; Goldmann, Wolfgang; Schröder, Rolf; Wiche, Gerhard (Journal of Clinical Investigation, 2014)
The ubiquitously expressed multifunctional cytolinker protein plectin is essential for muscle fiber integrity and myofiber cytoarchitecture. Patients suffering from plectinopathy-associated epidermolysis bullosa simplex with muscular dystrophy (EBS-MD) and mice lacking plectin in skeletal muscle display pathological desmin-positive protein aggregation and misalignment of Z-disks, which are hallmarks of myofibrillar myopathies (MFMs). Here, we developed immortalized murine myoblast cell lines to examine the pathogenesis of plectinopathies at the molecular and single cell level. Plectin-deficient myotubes, derived from myoblasts, were fully functional and mirrored the pathological features of EBS-MD myofibers, including the presence of desmin-positive protein aggregates and a concurrent disarrangement of the myofibrillar apparatus. Using this cell model, we demonstrated that plectin deficiency leads to increased intermediate filament network and sarcomere dynamics, marked upregulation of HSPs, and reduced myotube resilience following mechanical stretch. Currently, no specific therapy or treatment is available to improve plectin-related or other forms of MFMs; therefore, we assessed the therapeutic potential of chemical chaperones to relieve plectinopathies. Treatment with 4-phenylbutyrate resulted in remarkable amelioration of the pathological phenotypes in plectin-deficient myotubes as well as in plectin-deficient mice. Together, these data demonstrate the biological relevance of the MFM cell model and suggest that this model has potential use for the development of therapeutic approaches for EBS-MD.
EVALuna2:7203

Compound heterozygous RYR1 mutations in a preterm with arthrogryposis multiplex congenita and prenatal CNS bleeding - Brackmann, Florian; Türk, Matthias; Gratzki, Nils; Rompel, Oliver; Jungbluth, Heinz; Schröder, Rolf; Trollmann, Regina (Neuromuscular Disorders, 2018)
RYR1 mutations, the most common cause of non-dystrophic neuromuscular disorders, are associated with the malignant hyperthermia susceptibility (MHS) trait as well as congenital myopathies with widely variable clinical and histopathological manifestations. Recently, bleeding anomalies have been reported in association with certain RYR1 mutations. Here we report a preterm infant born at 32 weeks gestation with arthrogryposis multiplex congenita due to compound heterozygous, previously MHS-associated RYR1 mutations, with additional signs of prenatal hemorrhage. The patient presented at birth with multiple joint contractures, scoliosis, severe thoracic rigidity and respiratory failure. He continued to depend on mechanical ventilation and tube feeding. Muscle histopathology showed a marked myopathic pattern with eccentric cores. Interestingly, the patient had additional unusual prenatal intraventricular hemorrhage, resulting in post-hemorrhagic hydrocephalus as well as epidural hemorrhage affecting the spinal cord. This report adds to the phenotypic variability associated with RYR1 mutations, and highlights possible bleeding complications in affected individuals.
EVALuna2:34599

CRN2 binds to TIMP4 and MMP14 and promotes perivascular invasion of glioblastoma cells - Solga, Roxana; Behrens, Juliane; Ziemann, Anja; Riou, Adrien; Berwanger, Carolin; Becker, Lore; Garrett, Lillian; de Angelis, Martin Hrabe; Fischer, Lisa; Coras, Roland; Barkovits, Katalin; Marcus, Katrin; et al. (European Journal of Cell Biology, 2019)
CRN2 is an actin filament binding protein involved in the regulation of various cellular processes including cell migration and invasion. CRN2 has been implicated in the malignant progression of different types of human cancer. We used CRN2 knock-out mice for analyses as well as for crossbreeding with a Tp53/Pten knock-out glioblastoma mouse model. CRN2 knock-out mice were subjected to a phenotyping screen at the German Mouse Clinic. Murine glioblastoma tissue specimens as well as cultured murine brain slices and glioblastoma cell lines were investigated by immunohistochemistry, immunofluorescence, and cell biological experiments. Protein interactions were studied by immunoprecipitation, pull-down, and enzyme activity assays. CRN2 knock-out mice displayed neurological and behavioural alterations, e.g. reduced hearing sensitivity, reduced acoustic startle response, hypoactivity, and less frequent urination. While glioblastoma mice with or without the additional CRN2 knock-out allele exhibited no significant difference in their survival rates, the increased levels of CRN2 in transplanted glioblastoma cells caused a higher tumour cell encasement of murine brain slice capillaries. We identified two important factors of the tumour microenvironment, the tissue inhibitor of matrix metalloproteinase 4 (TIMP4) and the matrix metalloproteinase 14 (MMP14, synonym: MT1-MMP), as novel binding partners of CRN2. All three proteins mutually interacted and co-localised at the front of lamellipodia, and CRN2 was newly detected in exosomes. On the functional level, we demonstrate that CRN2 increased the secretion of TIMP4 as well as the catalytic activity of MMP14. Our results imply that CRN2 represents a pro-invasive effector within the tumour cell microenvironment of glioblastoma multiforme.
CRIS-Team Scopus Importer:2019-11-12
Keywords: Cancer; Coronin; Glioblastoma; Invasion; Metalloproteinases; Mouse model

Desmin Knock-Out Cardiomyopathy: A Heart on the Verge of Metabolic Crisis - Elsnicova, Barbara; Hornikova, Daniela; Tibenska, Veronika; Kolar, David; Tlapakova, Tereza; Schmid, Benjamin; Mallek, Markus; Eggers, Britta; Schlötzer-Schrehardt, Ursula; Peeva, Viktoriya; Berwanger, Carolin; Eberhard, Bettina; et al. (International Journal of Molecular Sciences, 2022)
Desmin mutations cause familial and sporadic cardiomyopathies. In addition to perturbing the contractile apparatus, both desmin deficiency and mutated desmin negatively impact mitochondria. Impaired myocardial metabolism secondary to mitochondrial defects could conceivably exacerbate cardiac contractile dysfunction. We performed metabolic myocardial phenotyping in left ventricular cardiac muscle tissue in desmin knock-out mice. Our analyses revealed decreased mitochondrial number, ultrastructural mitochondrial defects, and impaired mitochondria-related metabolic pathways including fatty acid transport, activation, and catabolism. Glucose transporter 1 and hexokinase-1 expression and hexokinase activity were increased. While mitochondrial creatine kinase expression was reduced, fetal creatine kinase expression was increased. Proteomic analysis revealed reduced expression of proteins involved in electron transport mainly of complexes I and II, oxidative phosphorylation, citrate cycle, beta-oxidation including auxiliary pathways, amino acid catabolism, and redox reactions and oxidative stress. Thus, desmin deficiency elicits a secondary cardiac mitochondriopathy with severely impaired oxidative phosphorylation and fatty and amino acid metabolism. Increased glucose utilization and fetal creatine kinase upregulation likely portray attempts to maintain myocardial energy supply. It may be prudent to avoid medications worsening mitochondrial function and other metabolic stressors. Therapeutic interventions for mitochondriopathies might also improve the metabolic condition in desmin deficient hearts.
CRIS-Team Scopus Importer:2022-10-28
Keywords: amino acid; cardiomyopathy; creatine kinase; desmin; desmin knock-out metabolism; desminopathy; fatty acid; glucose; mitochondria; mitochondriopathy

DesR349P Mutation Results in Ultrastructural Disruptions and Compromise of Skeletal Muscle Biomechanics Already at Preclinical Stages in Young Mice before the Onset of Protein Aggregation - Diermeier, Stefanie; Haug, Michael; Reischl, Barbara; Buttgereit, Andreas; Schürmann, Sebastian; Spörrer, Marina; Goldmann, Wolfgang; Fabry, Ben; Elhimine, F.; Stehle, Robert; Pfitzer, Gabriele; Winter, L.; et al. (Elsevier (Cell Press) / Biophysical Society, 2016)
Mutations in the extra-sarcomeric protein desmin give rise to protein aggregate myopathies that interfere with cellular function. The R350P mutation is the most common human desminopathy. A murine DesR349P model of human DesR350P desminopathy was previously engineered. In this study, we followed the hypothesis of whether muscle cytoarchitecture and biomechanical properties are already altered in preclinical stages of R349P desminopathy. We applied non-linear second harmonic generation (SHG) and 2-photon fluorescence morphometry analysis to single fibres of fast- and slow-twitch muscle to analyze sarcomeric architecture and nuclear morphology. We found a vast disruption of the lateral sarcomere lattice (indicated by large ‘vernier’ densities) and myofibrillar angular deviations (indicated by cosine angle sums) in single DesR349P fibres. Homozygous fibres were more severely affected than heterozygous. The former showed a marked nuclear pathology with spheric nuclei, increased nuclear number and density. For biomechanics, we assessed active and passive properties. Axial stiffness of DesR349P muscle was much increased, both in fibre and myofibrillar homozygous bundles. Lateral stiffness of the membrane complex in myoblasts was increased in cells heterozygous for DesR349P while homozygous were similar to wt. Caffeine-induced force was compromised in heterozygous fibre bundles but increased in homozygous bundles. This was explained by a marked shift of myofibrillar Ca2+ sensitivity: heterozygous bundles being less sensitive but homozygous more sensitive to Ca2+. This points towards a specific compensatory mechanism in homozygous mutation to cope with otherwise compromised force production already at preclinical stages of desminopathy. Our findings provide a very first complete picture to explain compromised force in heterozygous DesR350P patients: increased muscle stiffness, higher susceptibility towards stretch-induced injury, disrupted myofibrillar alignment and compromised active force productio

Diaphragmatic dysfunction as the presenting symptom in neuromuscular disorders: A retrospective longitudinal study of etiology and outcome in 30 German patients - Türk, Matthias; Weber, Irina; Vogt-Ladner, Gernot; Schröder, Rolf; Winterholler, Martin (Neuromuscular Disorders, 2018)
Diaphragmatic dysfunction is well-known in advanced stages of neuromuscular disorders. However, data on its presence as the presenting symptom in neuromuscular disorders is scarce. The goal of this retrospective longitudinal study was to evaluate the etiology and clinical outcome in patients, in whom uni- or bilateral diaphragmatic dysfunction was primarily diagnosed, before a specific neuromuscular disease was found. Patients with critical illness neuropathy/myopathy were excluded from this study. Analysis of the medical records of two tertiary referral centers for patients with neuromuscular diseases identified 30 corresponding patients with diaphragmatic dysfunction (17 unilateral; 13 bilateral). Phrenic neuropathy was found in 28 patients, one patient suffered from myasthenia gravis and another from Pompe disease. In 71% of patients with phrenic neuropathy a definite diagnosis could be established (iatrogenic lesion; amyotrophic lateral sclerosis; neuralgic amyotrophy; neuroborreliosis; multifocal motor neuropathy; chronic inflammatory demyelinating neuropathy; post-polio syndrome; spondylosis affecting the nerve root C4/5; and diabetes mellitus). When excluding all 5 patients with amyotrophic lateral sclerosis and further 3 with no follow-up data from outcome analysis, full or partial recovery was seen in 23% or 50% of patients, respectively. Early respiratory and electrophysiological work-ups are mandatory to ascertain the diagnosis and etiology of diaphragmatic dysfunction and to initiate therapy and counseling.
EVALuna2:34585

Disruptive recessive TTN missense mutations cause a wide range of clinico-pathological features - Rees, M.; Fukuzawa, A.; Nikoopour, R.; Kho, A.; Qi, J.; Fernandez-Garcia, M.; Wraige, E.; Cirak, S.; Pfuhl, M.; Fluss, J.; Muntoni, F.; Sarkozy, A.; et al. (NEUROMUSCULAR DISORDERS, 2019)
CRIS-Team WoS Importer:2019-10-11

Downstream effects of plectin mutations in epidermolysis bullosa simplex with muscular dystrophy - Winter, Lilli; Türk, Matthias; Harter, Patrick N.; Mittelbronn, Michel; Kornblum, Cornelia; Norwood, Fiona; Jungbluth, Heinz; Thiel, Christian; Schlötzer-Schrehardt, Ursula; Schröder, Rolf (Acta Neuropathologica Communications, 2016)
Mutations of the human plectin gene (PLEC) on chromosome 8q24 cause autosomal recessive epidermolysis bullosa simplex with muscular dystrophy (EBS-MD). In the present study we analyzed the downstream effects of PLEC mutations on plectin protein expression and localization, the structure of the extrasarcomeric desmin cytoskeleton, protein aggregate formation and mitochondrial distribution in skeletal muscle tissue from three EBS-MD patients. PLEC gene analysis in a not previously reported 35-year-old EBS-MD patient with additional disease features of cardiomyopathy and malignant arrhythmias revealed novel compound heterozygous (p.(Phe755del) and p.(Lys1040Argfs*139)) mutations resulting in complete abolition of plectin protein expression. In contrast, the other two patients with different homozygous PLEC mutations showed preserved plectin protein expression with one only expressing rodless plectin variants, and the other markedly reduced protein levels. Analysis of skeletal muscle tissue from all three patients revealed severe disruption of the extrasarcomeric intermediate filament cytoskeleton, protein aggregates positive for desmin, syncoilin, and synemin, degenerative myofibrillar changes, and mitochondrial abnormalities comprising respiratory chain dysfunction and an altered organelle distribution and amount.Our study demonstrates that EBS-MD causing PLEC mutations universally result in a desmin protein aggregate myopathy phenotype despite marked differences in individual plectin protein expression patterns. Since plectin is the key cytolinker protein that regulates the structural and functional organization of desmin filaments, the defective anchorage and spacing of assembled desmin filaments is the key pathogenetic event that triggers the formation of desmin protein aggregates as well as secondary mitochondrial pathology.
EVALuna2:7340

Dual Functional States of R406W-Desmin Assembly Complexes Cause Cardiomyopathy with Severe Intercalated Disc Derangement in Humans and in Knock-In Mice - Herrmann, Harald; Cabet, Eva; Chevalier, Nicolas R.; Moosmann, Julia; Schultheis, Dorothea; Haas, Jan; Schowalter, Mirjam; Berwanger, Carolin; Weyerer, Veronika; Agaimy, Abbas; Meder, Benjamin; Müller, Oliver J.; et al. (Circulation, 2020)
Background: Mutations in the human desmin gene cause myopathies and cardiomyopathies. This study aimed to elucidate molecular mechanisms initiated by the heterozygous R406W-desmin mutation in the development of a severe and early-onset cardiac phenotype. Methods: We report an adolescent patient who underwent cardiac transplantation as a result of restrictive cardiomyopathy caused by a heterozygous R406W-desmin mutation. Sections of the explanted heart were analyzed with antibodies specific to 406W-desmin and to intercalated disc proteins. Effects of the R406W mutation on the molecular properties of desmin were addressed by cell transfection and in vitro assembly experiments. To prove the genuine deleterious effect of the mutation on heart tissue, we further generated and analyzed R405W-desmin knock-in mice harboring the orthologous form of the human R406W-desmin. Results: Microscopic analysis of the explanted heart revealed desmin aggregates and the absence of desmin filaments at intercalated discs. Structural changes within intercalated discs were revealed by the abnormal organization of desmoplakin, plectin, N-cadherin, and connexin-43. Next-generation sequencing confirmed the DES variant c.1216C>T (p.R406W) as the sole disease-causing mutation. Cell transfection studies disclosed a dual behavior of R406W-desmin with both its integration into the endogenous intermediate filament system and segregation into protein aggregates. In vitro, R406W-desmin formed unusually thick filaments that organized into complex filament aggregates and fibrillar sheets. In contrast, assembly of equimolar mixtures of mutant and wild-type desmin generated chimeric filaments of seemingly normal morphology but with occasional prominent irregularities. Heterozygous and homozygous R405W-desmin knock-in mice develop both a myopathy and a cardiomyopathy. In particular, the main histopathologic results from the patient are recapitulated in the hearts from R405W-desmin knock-in mice of both genotypes. Moreover, whereas heterozygous knock-in mice have a normal life span, homozygous animals die at 3 months of age because of a smooth muscle-related gastrointestinal phenotype. Conclusions: We demonstrate that R406W-desmin provokes its severe cardiotoxic potential by a novel pathomechanism, where the concurrent dual functional states of mutant desmin assembly complexes underlie the uncoupling of desmin filaments from intercalated discs and their structural disorganization.
CRIS-Team Scopus Importer:2020-12-11
Keywords: cardiomyopathies; desmin; desmosomes; intermediate filaments; intestinal pseudo-obstruction; muscle; smooth; muscle; striated

Early signs of architectural and biomechanical failure in isolated myofibers and immortalized myoblasts from desmin-mutant knock-in mice - Diermeier, Stefanie; Iberl, Julian; Vetter, Karoline; Haug, Michael; Pollmann, Charlotte; Reischl, Barbara; Buttgereit, Andreas; Schürmann, Sebastian; Spörrer, Marina; Goldmann, Wolfgang; Fabry, Ben; Elhamine, Fatiha; et al. (Scientific Reports, 2017)
In striated muscle, desmin intermediate filaments interlink the contractile myofibrillar apparatus with mitochondria, nuclei, and the sarcolemma. The desmin network's pivotal role in myocytes is evident since mutations in the human desmin gene cause severe myopathies and cardiomyopathies. Here, we investigated skeletal muscle pathology in myofibers and myofibrils isolated from young hetero- and homozygous R349P desmin knock-in mice, which carry the orthologue of the most frequent human desmin missense mutation R350P. We demonstrate that mutant desmin alters myofibrillar cytoarchitecture, markedly disrupts the lateral sarcomere lattice and distorts myofibrillar angular axial orientation. Biomechanical assessment revealed a high predisposition to stretch-induced damage in fiber bundles of R349P mice. Notably, Ca(2)(+)-sensitivity and passive myofibrillar tension were decreased in heterozygous fiber bundles, but increased in homozygous fiber bundles compared to wildtype mice. In a parallel approach, we generated and subsequently subjected immortalized heterozygous R349P desmin knock-in myoblasts to magnetic tweezer experiments that revealed a significantly increased sarcolemmal lateral stiffness. Our data suggest that mutated desmin already markedly impedes myocyte structure and function at pre-symptomatic stages of myofibrillar myopathies.
EVALuna2:7360

Effect and safety of treatment with ACE-inhibitor Enalapril and β-blocker metoprolol on the onset of left ventricular dysfunction in Duchenne muscular dystrophy - A randomized, double-blind, placebo-controlled trial - Dittrich, Sven; Graf, Erika; Trollmann, Regina; Neudorf, Ulrich; Schara, Ulrike; Heilmann, Antje; Von Der Hagen, Maja; Stiller, Brigitte; Kirschner, Janbernd; Pozza, Robert Dalla; Müller-Felber, Wolfgang; Weiss, Katja; et al. (Orphanet Journal of Rare Diseases, 2019)
Background: X-linked Duchenne muscular dystrophy (DMD), the most frequent human hereditary skeletal muscle myopathy, inevitably leads to progressive dilated cardiomyopathy. We assessed the effect and safety of a combined treatment with the ACE-inhibitor enalapril and the β-blocker metoprolol in a German cohort of infantile and juvenile DMD patients with preserved left ventricular function. Methods Trial design: Sixteen weeks single-arm open run-in therapy with enalapril and metoprolol followed by a two-arm 1:1 randomized double-blind placebo-controlled treatment in a multicenter setting. Inclusion criteria: DMD boys aged 10-14 years with left ventricular fractional shortening [LV-FS] ≥ 30% in echocardiography. Primary endpoint: time from randomization to first occurrence of LV-FS < 28%. Secondary: changes of a) LV-FS from baseline, b) blood pressure, c), heart rate and autonomic function in ECG and Holter-ECG, e) cardiac biomarkers and neurohumeral serum parameters, f) quality of life, and g) adverse events. Results: From 3/2010 to 12/2013, 38 patients from 10 sites were centrally randomized after run-in, with 21 patients continuing enalapril and metoprolol medication and 17 patients receiving placebo. Until end of study 12/2015, LV-FS < 28% was reached in 6/21 versus 7/17 patients. Cox regression adjusted for LV-FS after run-in showed a statistically non-significant benefit for medication over placebo (hazard ratio: 0.38; 95% confidence interval: 0.12 to 1.22; p = 0.10). Analysis of secondary outcome measures revealed a time-dependent deterioration of LV-FS with no statistically significant differences between the two study arms. Blood pressure, maximal heart rate and mean-NN values were significantly lower at the end of open run-in treatment compared to baseline. Outcome analysis 19 months after randomization displayed significantly lower maximum heart rate and higher noradrenalin and renin values in the intervention group. No difference between treatments was seen for quality of life. As a single, yet important adverse event, the reversible deterioration of walking abilities of one DMD patient during the run-in period was observed. Conclusions: Our analysis of enalapril and metoprolol treatment in DMD patients with preserved left ventricular function is suggestive to delay the progression of the intrinsic cardiomyopathy to left ventricular failure, but did not reach statistical significance, probably due to insufficient sample size. Clinical trial registration: DRKS-number 00000115, EudraCT-number 2009-009871-36.
CRIS-Team Scopus Importer:2019-05-21
Keywords: ACE-inhibitors; Cardiomyopathy; Duchenne muscular dystrophy; ß-blockers

Ephedrine and 3,4 diaminopyridine responsive myasthenic syndrome in plectin-related epidermolysis bullosa simplex with muscular dystrophy - Argente-Escrig, H.; Gomez, N. Muelas; Gomez, L.; Türk, Matthias; Thiel, Christian; Schröder, Rolf; Vilchez, J. J. (2017)
EVALuna2:7354

Expression of N471D strumpellin leads to defects in the endolysosomal system - Song, Lin; Rijal, Ramesh; Karow, Matte; Stumpf, Maria; Hahn, Oliver; Park, Laura; Insall, Robert; Schröder, Rolf; Hofmann, Andreas; Clemen, Christoph S.; Eichinger, Ludwig (Disease Models & Mechanisms, 2018)
Hereditary spastic paraplegias (HSPs) are genetically diverse and clinically characterised by lower limb weakness and spasticity. The N471D and several other point mutations of human strumpellin (Str; also known as WASHC5), a member of the Wiskott-Aldrich syndrome protein and SCAR homologue (WASH) complex, have been shown to cause a form of HSP known as spastic paraplegia 8 (SPG8). To investigate the molecular functions of wild-type (WT) and N417D Str, we generated Dictyostelium Str- cells and ectopically expressed StrWT-GFP or StrN471D-GFP in Str- and WT cells. Overexpression of both proteins apparently caused a defect in cell division, as we observed a clear increase in multinucleate cells. Real-time PCR analyses revealed no transcriptional changes in WASH complex subunits in Str- cells, but western blots showed a twofold decrease in the SWIP subunit. GFP-trap experiments in conjunction with mass-spectrometric analysis revealed many previously known, as well as new, Str-interacting proteins, and also proteins that no longer bind to StrN471D At the cellular level, Str- cells displayed defects in cell growth, phagocytosis, macropinocytosis, exocytosis and lysosomal function. Expression of StrWT-GFP in Str- cells rescued all observed defects. In contrast, expression of StrN471D-GFP could not rescue lysosome morphology and exocytosis of indigestible material. Our results underscore a key role for the WASH complex and its core subunit, Str, in the endolysosomal system, and highlight the fundamental importance of the Str N471 residue for maintaining lysosome morphology and dynamics. Our data indicate that the SPG8-causing N471D mutation leads to a partial loss of Str function in the endolysosomal system. This article has an associated First Person interview with the first author of the paper.
EVALuna2:36584

Fiber Type-Specific Proteomic Alterations in R349P Desminopathy Mice - Eggers, Britta; Schork, Karin; Turewicz, Michael; Barkovits, Katalin; Eisenacher, Martin; Schröder, Rolf; Clemen, Christoph Stephan; Marcus, Katrin (Muscle & Nerve, 2025)
Introduction/Aims: Desminopathies are a group of rare human myopathies and cardiomyopathies caused by pathogenic variants of the desmin gene. Here, we analyzed the effects of the R349P mutant desmin on the proteomic profiles of individual fiber types of murine skeletal muscle. Methods: Soleus and tibialis anterior muscles from hetero- and homozygous R349P desmin knock-in mice and wild-type siblings were used to collect fiber type-specific material by laser microdissection to determine their proteomic profiles. Results: Aberrant proteomic profiles were observed in all four fiber types of homozygous mice. Type I and IIa fibers from homozygous muscle showed an increased abundance of 15 fibrotic proteins, for example, collagens I, IV, and VI, and associated proteins. Filamin-C, xin actin-binding repeat-containing proteins 1 and 2, and Kelch-like protein 41 were more abundant in homozygous fibers. A high number of proteins associated with the mitochondrial complexes had markedly lower amounts in all types of homozygous and type IIb heterozygous fibers, whereby 20 proteins of complex I, 6 proteins of complex III, 7 proteins of complex IV, and 4 proteins of complex V were found to be decreased in homozygous mice in at least one fiber type. This reduction included all mtDNA-encoded proteins of complexes I and V, as well as ADP/ATP translocase 1 and 2. Discussion: Our proteomic findings highlight a more severe myodegenerative process in fibers derived from homozygous R349P desmin knock-in mice. R349P desmin altered the abundance of proteins of the sarcomeric and extrasarcomeric cytoskeleton, extracellular matrix, and mitochondrial energy metabolism.
CRIS-Team Scopus Importer:2025-03-21
Keywords: desminopathy; fiber types; laser microdissection; proteomics; skeletal muscle

Genetic analysis of VCP and WASH complex genes in a German cohort of sporadic ALS-FTD patients - Türk, Matthias; Schröder, Rolf; Khuller, Katharina; Hofmann, Andreas; Berwanger, Carolin; Ludolph, Albert C.; Dekomien, Gabriele; Mueller, Kathrin; Weishaupt, Jochen H.; Thiel, Christian; Clemen, Christoph S. (Neurobiology of Aging, 2017)
Mutations of the human valosin-containing protein, p97 (VCP) and Wiskott-Aldrich syndrome protein and SCAR homolog (WASH) complex genes cause motor neuron and cognitive impairment disorders. Here, we analyzed a cohort of German patients with sporadic amyotrophic lateral sclerosis and frontotemporal lobar degeneration comorbidity (ALS/FTD) for VCP and WASH complex gene mutations. Next-generation panel sequencing of VCP, WASH1, FAM21C, CCDC53, SWIP, strumpellin, F-actin capping protein of muscle Z-line alfa 1 (CAPZA1), and CAPZB genes was performed in 43 sporadic ALS/FTD patients. Subsequent analyses included Sanger sequencing, in silico analyses, real-time PCR, and CCDC53 immunoblotting. We identified 1 patient with the heterozygous variant c.26C>T in CAPZA1, predicted to result in p.Ser9Leu, and a second with the heterozygous start codon variant c.2T>C in CCDC53. In silico analysis predicted structural changes in the N-terminus of CAPZ?1, which may interfere with CAPZ?:CAPZ? dimerization. Though the translation initiation codon of CCDC53 is mutated, real-time PCR and immunoblotting did neither reveal any evidence for a CCDC53 haploinsufficiency nor for aberrant CCDC53 protein species. Moreover, a disease-causing C9orf72 repeat expansion mutation was later on identified in this patient. Thus, with the exception of a putatively pathogenic heterozygous c.26C>T CAPZA1 variant, our genetic analysis did not reveal mutations in VCP and the remaining WASH complex subunits.
EVALuna2:7373

Growing old too early: Skeletal muscle single fiber biomechanics in ageing r349p desmin knock-in mice using the myorobot technology - Pollmann, Charlotte; Haug, Michael; Reischl, Barbara; Prölß, Gerhard; Pöschel, Thorsten; Rupitsch, Stefan; Clemen, Christoph S.; Schröder, Rolf; Friedrich, Oliver (International Journal of Molecular Sciences, 2020)
Muscle biomechanics relies on active motor protein assembly and passive strain transmission through cytoskeletal structures. The desmin filament network aligns myofibrils at the z-discs, provides nuclear–sarcolemmal anchorage and may also serve as memory for muscle repositioning following large strains. Our previous analyses of R349P desmin knock-in mice, an animal model for the human R350P desminopathy, already depicted pre-clinical changes in myofibrillar arrangement and increased fiber bundle stiffness. As the effect of R349P desmin on axial biomechanics in fully differentiated single muscle fibers is unknown, we used our MyoRobot to compare passive visco-elasticity and active contractile biomechanics in single fibers from fast-and slow-twitch muscles from adult to senile mice, hetero-or homozygous for the R349P desmin mutation with wild type littermates. We demonstrate that R349P desmin presence predominantly increased axial stiffness in both muscle types with a pre-aged phenotype over wild type fibers. Axial viscosity and Ca2+-mediated force were largely unaffected. Mutant single fibers showed tendencies towards faster unloaded shortening over wild type fibers. Effects of aging seen in the wild type appeared earlier in the mutant desmin fibers. Our single-fiber experiments, free of extracellular matrix, suggest that compromised muscle biomechanics is not exclusively attributed to fibrosis but also originates from an impaired intermediate filament network.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Biomechatronics; Desminopathy; R349P desmin; Single fibers; Skeletal muscle

Heart failure after pressure overload in autosomal-dominant desminopathies: Lessons from heterozygous DES-p.R349P knock-in mice - Stöckigt, Florian; Eichhorn, Lars; Beiert, Thomas; Knappe, Vincent; Radecke, Tobias; Steinmetz, Martin; Nickenig, Georg; Peeva, Viktoriya; Kudin, Alexei P.; Kunz, Wolfram S.; Berwanger, Carolin; Kamm, Lisa; et al. (PLoS ONE, 2020)
Background Mutations in the human desmin gene (DES) cause autosomal-dominant and -recessive cardiomyopathies, leading to heart failure, arrhythmias, and AV blocks. We analyzed the effects of vascular pressure overload in a patient-mimicking p.R349P desmin knock-in mouse model that harbors the orthologue of the frequent human DES missense mutation p. R350P. Methods and results Transverse aortic constriction (TAC) was performed on heterozygous (HET) DES-p.R349P mice and wild-type (WT) littermates. Echocardiography demonstrated reduced left ventricular ejection fraction in HET-TAC (WT-sham: 69.5 ± 2.9%, HET-sham: 64.5 ± 4.7%, WTTAC: 63.5 ± 4.9%, HET-TAC: 55.7 ± 5.4%; p<0.01). Cardiac output was significantly reduced in HET-TAC (WT sham: 13088 ± 2385 μl/min, HET sham: 10391 ± 1349μl/min, WT-TAC: 8097 ± 1903μl/min, HET-TAC: 5793 ± 2517μl/min; p<0.01). Incidence and duration of AV blocks as well as the probability to induce ventricular tachycardias was highest in HET-TAC. We observed reduced mtDNA copy numbers in HET-TAC (WT-sham: 12546 ± 406, HET-sham: 13526 ± 781, WT-TAC: 11155 ± 3315, HET-TAC: 8649 ± 1582; p = 0.025), but no mtDNA deletions. The activity of respiratory chain complexes I and IV showed the greatest reductions in HET-TAC. Conclusion Pressure overload in HET mice aggravated the clinical phenotype of cardiomyopathy and resulted in mitochondrial dysfunction. Preventive avoidance of pressure overload/arterial hypertension in desminopathy patients might represent a crucial therapeutic measure.
CRIS-Team Scopus Importer:2020-03-17

Hereditary myopathy with early respiratory failure: occurrence in various populations - Palmio, Johanna; Evila, Anni; Chapon, Francoise; Tasca, Giorgio; Xiang, Fengqing; Bradvik, Bjorn; Eymard, Bruno; Echaniz-Laguna, Andoni; Laporte, Jocelyn; Karppa, Mikko; Mahjneh, Ibrahim; Quinlivan, Rosaline; et al. (Journal of Neurology Neurosurgery and Psychiatry, 2014)
Several families with characteristic features of hereditary myopathy with early respiratory failure (HMERF) have remained without genetic cause. This international study was initiated to clarify epidemiology and the genetic underlying cause in these families, and to characterise the phenotype in our large cohort.DNA samples of all currently known families with HMERF without molecular genetic cause were obtained from 12 families in seven different countries. Clinical, histopathological and muscle imaging data were collected and five biopsy samples made available for further immunohistochemical studies. Genotyping, exome sequencing and Sanger sequencing were used to identify and confirm sequence variations.All patients with clinical diagnosis of HMERF were genetically solved by five different titin mutations identified. One mutation has been reported while four are novel, all located exclusively in the FN3 119 domain (A150) of A-band titin. One of the new mutations showed semirecessive inheritance pattern with subclinical myopathy in the heterozygous parents. Typical clinical features were respiratory failure at mid-adulthood in an ambulant patient with very variable degree of muscle weakness. Cytoplasmic bodies were retrospectively observed in all muscle biopsy samples and these were reactive for myofibrillar proteins but not for titin.We report an extensive collection of families with HMERF with five different mutations in exon 343 of TTN, which establishes this exon as the primary target for molecular diagnosis of HMERF. Our relatively large number of new families and mutations directly implies that HMERF is not extremely rare, not restricted to Northern Europe and should be considered in undetermined myogenic respiratory failure.
EVALuna2:7204

Homozygous expression of the myofibrillar myopathy-associated p.W2710X filamin C variant reveals major pathomechanisms of sarcomeric lesion formation - Schuld, Julia; Orfanos, Zacharias; Chevessier, Frederic; Eggers, Britta; Heil, Lorena; Uszkoreit, Julian; Unger, Andreas; Kirfel, Gregor; van der Ven, Peter F.M.; Marcus, Katrin; Linke, Wolfgang A.; Clemen, Christoph S.; et al. (Acta Neuropathologica Communications, 2020)
Filamin C (FLNc) is mainly expressed in striated muscle cells where it localizes to Z-discs, myotendinous junctions and intercalated discs. Recent studies have revealed numerous mutations in the FLNC gene causing familial and sporadic myopathies and cardiomyopathies with marked clinical variability. The most frequent myopathic mutation, p.W2710X, which is associated with myofibrillar myopathy, deletes the carboxy-terminal 16 amino acids from FLNc and abolishes the dimerization property of Ig-like domain 24. We previously characterized "knock-in" mice heterozygous for this mutation (p.W2711X), and have now investigated homozygous mice using protein and mRNA expression analyses, mass spectrometry, and extensive immunolocalization and ultrastructural studies. Although the latter mice display a relatively mild myopathy under normal conditions, our analyses identified major mechanisms causing the pathophysiology of this disease: in comparison to wildtype animals (i) the expression level of FLNc protein is drastically reduced; (ii) mutant FLNc is relocalized from Z-discs to particularly mechanically strained parts of muscle cells, i.e. myotendinous junctions and myofibrillar lesions; (iii) the number of lesions is greatly increased and these lesions lack Bcl2-associated athanogene 3 (BAG3) protein; (iv) the expression of heat shock protein beta-7 (HSPB7) is almost completely abolished. These findings indicate grave disturbances of BAG3-dependent and -independent autophagy pathways that are required for efficient lesion repair. In addition, our studies reveal general mechanisms of lesion formation and demonstrate that defective FLNc dimerization via its carboxy-terminal domain does not disturb assembly and basic function of myofibrils. An alternative, more amino-terminally located dimerization site might compensate for that loss. Since filamins function as stress sensors, our data further substantiate that FLNc is important for mechanosensing in the context of Z-disc stabilization and maintenance.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Autophagy; BAG3; Filamin; HSPB7; Mouse model; Muscle damage; Myofibrillar lesions; Myofibrillar myopathy; Pathophysiology

Imbalances in protein homeostasis caused by mutant desmin - Clemen, C.; Winter, L.; Unger, A.; Berwanger, C.; Spörrer, Marina; Linke, W.; Schröder, Rolf (NEUROMUSCULAR DISORDERS, 2019)
CRIS-Team WoS Importer:2019-10-11

Imbalances in protein homeostasis caused by mutant desmin - Winter, L.; Unger, A.; Berwanger, C.; Spörrer, Marina; Türk, Matthias; Chevessier, Frederic; Strucksberg, K. H.; Schlötzer-Schrehardt, Ursula; Wittig, I.; Goldmann, Wolfgang; Marcus, K.; Linke, W. A.; et al. (Neuropathology and Applied Neurobiology, 2019)
Aims: We investigated newly generated immortalized heterozygous and homozygous R349P desmin knock-in myoblasts in conjunction with the corresponding desminopathy mice as models for desminopathies to analyse major protein quality control processes in response to the presence of R349P mutant desmin. Methods: We used hetero- and homozygous R349P desmin knock-in mice for analyses and for crossbreeding with p53 knock-out mice to generate immortalized R349P desmin knock-in skeletal muscle myoblasts and myotubes. Skeletal muscle sections and cultured muscle cells were investigated by indirect immunofluorescence microscopy, proteasomal activity measurements and immunoblotting addressing autophagy rate, chaperone-assisted selective autophagy and heat shock protein levels. Muscle sections were further analysed by transmission and immunogold electron microscopy. Results: We demonstrate that mutant desmin (i) increases proteasomal activity, (ii) stimulates macroautophagy, (iii) dysregulates the chaperone assisted selective autophagy and (iv) elevates the protein levels of αB-crystallin and Hsp27. Both αB-crystallin and Hsp27 as well as Hsp90 displayed translocation patterns from Z-discs as well as Z-I junctions, respectively, to the level of sarcomeric I-bands in dominant and recessive desminopathies. Conclusions: Our findings demonstrate that the presence of R349P mutant desmin causes a general imbalance in skeletal muscle protein homeostasis via aberrant activity of all major protein quality control systems. The augmented activity of these systems and the subcellular shift of essential heat shock proteins may deleteriously contribute to the previously observed increased turnover of desmin itself and desmin-binding partners, which triggers progressive dysfunction of the extrasarcomeric cytoskeleton and the myofibrillar apparatus in the course of the development of desminopathies.
CRIS-Team Scopus Importer:2019-07-30
Keywords: desminopathy; immortalized myoblasts; protein homeostasis; protein quality control; R349P desmin knock-in mice

Immortalised murine R349P desmin knock-in myotubes exhibit a reduced proton leak and decreased ADP/ATP translocase levels in purified mitochondria - Berwanger, Carolin; Terres, Dominic; Pesta, Dominik; Eggers, Britta; Marcus, Katrin; Wittig, Ilka; Wiesner, Rudolf J.; Schröder, Rolf; Clemen, Christoph S. (European Journal of Cell Biology, 2024)
Desmin gene mutations cause myopathies and cardiomyopathies. Our previously characterised R349P desminopathy mice, which carry the ortholog of the common human desmin mutation R350P, showed marked alterations in mitochondrial morphology and function in muscle tissue. By isolating skeletal muscle myoblasts from offspring of R349P desminopathy and p53 knock-out mice, we established an immortalised cellular disease model. Heterozygous and homozygous R349P desmin knock-in and wild-type myoblasts could be well differentiated into multinucleated spontaneously contracting myotubes. The desminopathy myoblasts showed the characteristic disruption of the desmin cytoskeleton and desmin protein aggregation, and the desminopathy myotubes showed the characteristic myofibrillar irregularities. Long-term electrical pulse stimulation promoted myotube differentiation and markedly increased their spontaneous contraction rate. In both heterozygous and homozygous R349P desminopathy myotubes, this treatment restored a regular myofibrillar cross-striation pattern as seen in wild-type myotubes. High-resolution respirometry of mitochondria purified from myotubes by density gradient ultracentrifugation revealed normal oxidative phosphorylation capacity, but a significantly reduced proton leak in mitochondria from the homozygous R349P desmin knock-in cells. Consistent with a reduced proton flux across the inner mitochondrial membrane, our quantitative proteomic analysis of the purified mitochondria revealed significantly reduced levels of ADP/ATP translocases in the homozygous R349P desmin knock-in genotype. As this alteration was also detected in the soleus muscle of R349P desminopathy mice, which, in contrast to the mitochondria purified from cultured cells, showed a variety of other dysregulated mitochondrial proteins, we consider this finding to be an early step in the pathogenesis of secondary mitochondriopathy in desminopathy.
CRIS-Team Scopus Importer:2024-03-15
Keywords: ADP/ATP translocase; Desminopathy; Electrical pulse stimulation; Immortalised murine myoblasts; Mitochondrial respiration; Myofibrillar maturation

Inclusion Body Myopathy, Paget's Disease, and Fronto-temporal Dementia: a VCP-related Multi-systemic Proteinopathy - Mengel, David; Librizzi, Damiano; Schoser, Benedikt; Glaeser, Dieter; Clemen, Christoph S.; Dodel, Richard; Schröder, Rolf (Fortschritte der Neurologie - Psychiatrie, 2018)
Mutations of the human VCP gene, which encodes the V: alosin C: ontaining P: rotein (synonyms: p97, TER ATPase), are associated with various multi-systemic protein aggregation diseases. We report on a patient with progressive myopathy and incipient cognitive deficits. A diagnostic muscle biopsy revealed an inclusion body myopathy with protein aggregates. Magnetic resonance imaging and F18-positron-emission-tomography disclosed a fronto-temporal atrophy and glucose hypometabolism of the frontal and temporal lobes, respectively. Based on the clinical findings, a genetic analysis was performed which revealed a heterozygous c.277C>T (p.Arg93Cys) mutation of the VCP gene, thus confirming the diagnosis of IBMPFD (I: nclusion B: ody M: yopathie with P: aget Disease of the Bones and F: ronto-temporal D: ementia).
EVALuna2:34584

In vivo characterization of human myofibrillar myopathy genes in zebrafish - Buehrdel, John B.; Hirth, Sofia; Kessler, Mirjam; Westphal, Soeren; Forster, Monika; Manta, Linda; Wiche, Gerhard; Schoser, Benedikt; Schessl, Joachim; Schröder, Rolf; Clemen, Christoph S.; Eichinger, Ludwig; et al. (Biochemical and Biophysical Research Communications, 2015)
Myofibrillar myopathies (MFM) are progressive diseases of human heart and skeletal muscle with a severe impact on life quality and expectancy of affected patients. Although recently several disease genes for myofibrillar myopathies could be identified, today most genetic causes and particularly the associated mechanisms and signaling events that lead from the mutation to the disease phenotype are still mostly unknown. To assess whether the zebrafish is a suitable model system to validate MFM candidate genes using targeted antisense-mediated knock-down strategies, we here specifically inactivated known human MFM disease genes and evaluated the resulting muscular and cardiac phenotypes functionally and structurally. Consistently, targeted ablation of MFM genes in zebrafish led to compromised skeletal muscle function mostly due to myofibrillar degeneration as well as severe heart failure. Similar to what was shown in MFM patients, MFM gene-deficient zebrafish showed pronounced gene-specific phenotypic and structural differences. In summary, our results indicate that the zebrafish is a suitable model to functionally and structurally evaluate novel MFM disease genes in vivo.
EVALuna2:7288

Lack of Desmin in Mice Causes Structural and Functional Disorders of Neuromuscular Junctions - Eiber, Nane; Fröb, Franziska; Schowalter, Mirjam; Thiel, Christian; Clemen, Christoph S.; Schröder, Rolf; Hashemolhosseini, Said (Frontiers in Molecular Neuroscience, 2020)
Desmin, the major intermediate filament (IF) protein in muscle cells, interlinks neighboring myofibrils and connects the whole myofibrillar apparatus to myonuclei, mitochondria, and the sarcolemma. However, desmin is also known to be enriched at postsynaptic membranes of neuromuscular junctions (NMJs). The pivotal role of the desmin IF cytoskeletal network is underscored by the fact that over 120 mutations of the human DES gene cause hereditary and sporadic myopathies and cardiomyopathies. A subgroup of human desminopathies comprises autosomal recessive cases resulting in the complete abolition of desmin protein. In these patients, who display a more severe phenotype than the autosomal dominant cases, it has been reported that some individuals also suffer from a myasthenic syndrome in addition to the classical occurrence of myopathy and cardiomyopathy. Since further studies on the NMJ pathology are hampered by the lack of available human striated muscle biopsy specimens, we exploited homozygous desmin knock-out mice which closely mirror the striated muscle pathology of human patients lacking desmin protein. Here, we report on the impact of the lack of desmin on the structure and function of NMJs and the transcription of genes coding for postsynaptic proteins. Desmin knock-out mice display a fragmentation of NMJs in soleus, but not in the extensor digitorum longus muscle. Moreover, soleus muscle fibers show larger NMJs. Further, transcription levels of acetylcholine receptor (AChR) genes are increased in muscles from desmin knock-out mice, especially of the AChR gamma subunit, which is known as a marker of muscle fiber regeneration. Electrophysiological recordings depicted a pathological decrement of nerve-dependent endplate potentials and an increased rise time of the nerve-independent miniature endplate potentials. The latter appears related to the fragmentation of NMJs in desmin knockout mice. Our study highlights the essential role of desmin for the structural and functional integrity of mammalian NMJs.
CRIS-Team WoS Importer:2020-11-27

Loss of the novel Vcp (valosin containing protein) interactor Washc4 interferes with autophagy-mediated proteostasis in striated muscle and leads to myopathy in vivo - Kustermann, Monika; Manta, Linda; Paone, Christoph; Kustermann, Jochen; Lausser, Ludwig; Wiesner, Cora; Eichinger, Ludwig; Clemen, Christoph S.; Schröder, Rolf; Kestler, Hans A.; Sandri, Marco; Rottbauer, Wolfgang; et al. (Autophagy, 2018)
VCP/p97 (valosin containing protein) is a key regulator of cellular proteostasis. It orchestrates protein turnover and quality control in vivo, processes fundamental for proper cell function. In humans, mutations in VCP lead to severe myo- and neuro-degenerative disorders such as inclusion body myopathy with Paget disease of the bone and frontotemporal dementia (IBMPFD), amyotrophic lateral sclerosis (ALS) or and hereditary spastic paraplegia (HSP). We analyzed here the in vivo role of Vcp and its novel interactor Washc4/Swip (WASH complex subunit 4) in the vertebrate model zebrafish (Danio rerio). We found that targeted inactivation of either Vcp or Washc4, led to progressive impairment of cardiac and skeletal muscle function, structure and cytoarchitecture without interfering with the differentiation of both organ systems. Notably, loss of Vcp resulted in compromised protein degradation via the proteasome and the macroautophagy/autophagy machinery, whereas Washc4 deficiency did not affect the function of the ubiquitin-proteasome system (UPS) but caused ER stress and interfered with autophagy function in vivo. In summary, our findings provide novel insights into the in vivo functions of Vcp and its novel interactor Washc4 and their particular and distinct roles during proteostasis in striated muscle cells.
EVALuna2:36586

Making sense of missense variants in TTN-related congenital myopathies - Rees, Martin; Nikoopour, Roksana; Fukuzawa, Atsushi; Kho, Ay Lin; Fernandez-Garcia, Miguel A.; Wraige, Elizabeth; Bodi, Istvan; Deshpande, Charu; Oezdemir, Oezkan; Daimagueler, Hulya-Sevcan; Pfuhl, Mark; Holt, Mark; et al. (Acta Neuropathologica, 2021)
Mutations in the sarcomeric protein titin, encoded by TTN, are emerging as a common cause of myopathies. The diagnosis of a TTN-related myopathy is, however, often not straightforward due to clinico-pathological overlap with other myopathies and the prevalence of TTN variants in control populations. Here, we present a combined clinico-pathological, genetic and biophysical approach to the diagnosis of TTN-related myopathies and the pathogenicity ascertainment of TTN missense variants. We identified 30 patients with a primary TTN-related congenital myopathy (CM) and two truncating variants, or one truncating and one missense TTN variant, or homozygous for one TTN missense variant. We found that TTN-related myopathies show considerable overlap with other myopathies but are strongly suggested by a combination of certain clinico-pathological features. Presentation was typically at birth with the clinical course characterized by variable progression of weakness, contractures, scoliosis and respiratory symptoms but sparing of extraocular muscles. Cardiac involvement depended on the variant position. Our biophysical analyses demonstrated that missense mutations associated with CMs are strongly destabilizing and exert their effect when expressed on a truncating background or in homozygosity. We hypothesise that destabilizing TTN missense mutations phenocopy truncating variants and are a key pathogenic feature of recessive titinopathies that might be amenable to therapeutic intervention.
CRIS-Team WoS Importer:2021-01-29

Malignant cardiac phenotype after pressure overload in autosomal-dominant desminopathies: Lessons from heterozygous R349P desmin knock-in mice - Stoeckigt, F.; Eichhorn, L.; Beiert, T.; Knappe, V.; Radecke, T.; Steinmetz, M.; Berwanger, C.; Nickenig, G.; Peeva, V.; Kunz, W.; Clemen, C.; Schröder, Rolf; et al. (NEUROMUSCULAR DISORDERS, 2019)
CRIS-Team WoS Importer:2019-10-11

Mutant p97 exhibits species-specific changes of its ATPase activity and compromises the UBXD9-mediated monomerisation of p97 hexamers - Rijal, Ramesh; Arhzaouy, Khalid; Strucksberg, Karl-Heinz; Cross, Megan; Hofmann, Andreas; Schröder, Rolf; Clemen, Christoph S.; Eichinger, Ludwig (European Journal of Cell Biology, 2016)
p97 (VCP) is a homo-hexameric triple-A ATPase that exerts a plethora of cellular processes. Heterozygous missense mutations of p97 cause at least five human neurodegenerative disorders. However, the specific molecular consequences of p97 mutations are hitherto widely unknown. Our in silico structural models of human and Dictyostelium p97 showed that the disease-causing human R93C, R155H, and R155C as well as Dictyostelium R154C, E219K, R154C/E219K p97 mutations constitute variations in surface-exposed locations. In-gel ATPase activity measurements of p97 monomers and hexamers revealed significant mutation- and species-specific differences. While all human p97 mutations led to an increase in ATPase activity, no changes could be detected for the Dictyostelium R154C mutant, which is orthologous to human R155C. The E219K mutation led to an almost complete loss of activity, which was partially recuperated in the R154C/E219K double-mutant indicating p97 inter-domain communication. By means of co-immunoprecipitation experiments we identified an UBX-domain containing Dictyostelium protein as a novel p97 interaction partner. We categorized all UBX-domain containing Dictyostelium proteins and named the interaction partner UBXD9. Pull-down assays and surface plasmon resonance analyses of Dictyostelium UBXD9 or the human orthologue TUG/ASPL/UBXD9 demonstrated direct interactions with p97 as well as species-, mutation- and ATP-dependent differences in the binding affinities. Sucrose density gradient assays revealed that both human and Dictyostelium UBXD9 proteins very efficiently disassembled wild-type, but to a lesser extent mutant p97 hexamers into monomers. Our results are consistent with a scenario in which p97 point mutations lead to differences in enzymatic activities and molecular interactions, which in the long-term result in a late-onset and progressive multisystem disease.
EVALuna2:7334

Myofibrillar instability exacerbated by acute exercise in filaminopathy - Chevessier, Frederic; Schuld, Julia; Orfanos, Zacharias; Plank, Anne-Christine; Wolf, Lucie; Maerkens, Alexandra; Unger, Andreas; Schlötzer-Schrehardt, Ursula; Kley, Rudolf A.; von Hörsten, Stephan; Marcus, Katrin; Linke, Wolfgang A.; et al. (Human Molecular Genetics, 2015)
Filamin C (FLNC) mutations in humans cause myofibrillar myopathy (MFM) and cardiomyopathy, characterized by protein aggregation and myofibrillar degeneration. We generated the first patient-mimicking knock-in mouse harbouring the most common disease-causing filamin C mutation (p.W2710X). These heterozygous mice developed muscle weakness and myofibrillar instability, with formation of filamin C- and Xin-positive lesions streaming between Z-discs. These lesions, which are distinct from the classical MFM protein aggregates by their morphology and filamentous appearance, were greatly increased in number upon acute physical exercise in the mice. This pathology suggests that mutant filamin influences the mechanical stability of myofibrillar Z-discs, explaining the muscle weakness in mice and humans. Re-evaluation of biopsies from MFM-filaminopathy patients with different FLNC mutations revealed a similar, previously unreported lesion pathology, in addition to the classical protein aggregates, and suggested that structures previously interpreted as aggregates may be in part sarcomeric lesions. We postulate that these lesions define preclinical disease stages, preceding the formation of protein aggregates.
EVALuna2:7293

Myositis and neuromuscular side-effects induced by immune checkpoint inhibitors - Moreira, Alvaro; Loquai, Carmen; Pfoefer, Claudia; Kaehler, Katharina C.; Knauss, Samuel; Heppt, Markus V.; Gutzmer, Ralf; Dimitriou, Florentia; Meier, Friedegund; Mitzel-Rink, Heidrun; Schuler, Gerold; Terheyden, Patrick; et al. (European Journal of Cancer, 2019)
AIM: To characterise clinical presentation, laboratory and histopathologic characteristics and assess the treatment and outcome of neuromuscular side-effects of checkpoint therapy. METHODS: The side-effect registry and the institutional database from ten skin cancer centres were queried for reports on myositis and neuromuscular side-effects induced by checkpoint inhibitors. In total, 38 patients treated with ipilimumab, tremelimumab, nivolumab and pembrolizumab for metastatic skin cancer were evaluated and characterised. RESULTS: Myositis was the most frequent neuromuscular adverse event. In 32% of cases, myositis was complicated by concomitant myocarditis. Furthermore, cases of isolated myocarditis, myasthenia gravis, polymyalgia rheumatica, radiculoneuropathy and asymptomatic creatine kinase elevation were reported. The onset of side-effects ranged from the first week of treatment to 115 weeks after the start of therapy. Most of the cases were severe (49% grade III-IV Common Terminology Criteria for Adverse Events), and there were two fatalities (5%) due to myositis and myositis with concomitant myocarditis. Only half of the cases (50%) completely resolved, whereas the rest was either ongoing or had sequelae. Steroids were given in 80% of the resolved cases and in 40% of the unresolved cases. CONCLUSION: Immune-mediated neuromuscular side-effects of checkpoint inhibitors greatly vary in presentation and differ from their idiopathic counterparts. These side-effects can be life threatening and may result in permanent sequelae. Occurrence of these side-effects must be taken into consideration for patient information, especially when considering adjuvant immunotherapy with anti-programmed cell-death protein 1 (PD-1) antibodies and monitoring, which should include regular surveillance of creatine kinase.
EVALuna2:36556

N471D WASH complex subunit strumpellin knock-in mice display mild motor and cardiac abnormalities and BPTF and KLHL11 dysregulation in brain tissue - Clemen, Christoph S.; Schmidt, Andreas; Winter, Lilli; Canneva, Fabio; Wittig, Ilka; Becker, Lore; Coras, Roland; Berwanger, Carolin; Hofmann, Andreas; Eggers, Britta; Marcus, Katrin; Gailus-Durner, Valerie; et al. (Neuropathology and Applied Neurobiology, 2021)
Aims We investigated N471D WASH complex subunit strumpellin (Washc5) knock-in and Washc5 knock-out mice as models for hereditary spastic paraplegia type 8 (SPG8). Methods We generated heterozygous and homozygous N471D Washc5 knock-in mice and subjected them to a comprehensive clinical, morphological and laboratory parameter screen, and gait analyses. Brain tissue was used for proteomic analysis. Furthermore, we generated heterozygous Washc5 knock-out mice. WASH complex subunit strumpellin expression was determined by qPCR and immunoblotting. Results Homozygous N471D Washc5 knock-in mice showed mild dilated cardiomyopathy, decreased acoustic startle reactivity, thinner eye lenses, increased alkaline phosphatase and potassium levels and increased white blood cell counts. Gait analyses revealed multiple aberrations indicative of locomotor instability. Similarly, the clinical chemistry, haematology and gait parameters of heterozygous mice also deviated from the values expected for healthy animals, albeit to a lesser extent. Proteomic analysis of brain tissue depicted consistent upregulation of BPTF and downregulation of KLHL11 in heterozygous and homozygous knock-in mice. WASHC5-related protein interaction partners and complexes showed no change in abundancies. Heterozygous Washc5 knock-out mice showing normal WASHC5 levels could not be bred to homozygosity. Conclusions While biallelic ablation of Washc5 was prenatally lethal, expression of N471D mutated WASHC5 led to several mild clinical and laboratory parameter abnormalities, but not to a typical SPG8 phenotype. The consistent upregulation of BPTF and downregulation of KLHL11 suggest mechanistic links between the expression of N471D mutated WASHC5 and the roles of both proteins in neurodegeneration and protein quality control, respectively.
CRIS-Team WoS Importer:2021-08-27

Neuromuscular endplate pathology in recessive desminopathies: Lessons from man and mice - Durmus, Hacer; Ayhan, Ozgecan; Cirak, Sebahattin; Deymeer, Feza; Parman, Yesim; Franke, Andre; Eiber, Nane; Chevessier, Frederic; Schlötzer-Schrehardt, Ursula; Clemen, Christoph S.; Hashemolhosseini, Said; Schröder, Rolf; et al. (Neurology, 2016)
To assess the clinical, genetic, and myopathologic findings in 2 cousins with lack of desmin, the response to salbutamol in one patient, and the neuromuscular endplate pathology in a knock-in mouse model for recessive desminopathy.We performed clinical investigations in the patients, genetic studies for linkage mapping, exome sequencing, and qPCR for transcript quantification, assessment of efficacy of (3-month oral) salbutamol administration by muscle strength assessment, 6-minute walking test (6MWT), and forced vital capacity, analysis of neuromuscular endplate pathology in a homozygous R349P desmin knock-in mouse by immunofluorescence staining of the hind limb muscles, and quantitative 3D morphometry and expression studies of acetylcholine receptor genes by quantitative PCR.Both patients had infantile-onset weakness and fatigability, facial weakness with bilateral ptosis and ophthalmoparesis, generalized muscle weakness, and a decremental response over 10% on repetitive nerve stimulation. Salbutamol improved 6MWT and subjective motor function in the treated patient. Genetic analysis revealed previously unreported novel homozygous truncating desmin mutation c.345dupC leading to protein truncation and consequent fast degradation of the mutant mRNA. In the recessive desminopathy mouse with low expression of the mutant desmin protein, we demonstrated fragmented motor endplates with increased surface areas, volumes, and fluorescence intensities in conjunction with increased ? and ? acetylcholine receptor subunit expression in oxidative soleus muscle.The patients were desmin-null and had myopathy, cardiomyopathy, and a congenital myasthenic syndrome. The data from man and mouse demonstrate that the complete lack as well as the markedly decreased expression of mutant R349P desmin impair the structural and functional integrity of neuromuscular endplates.
EVALuna2:4994

Neuronal VCP loss of function recapitulates FTLD-TDP pathology - Wani, Abubakar; Zhu, Jiang; Ulrich, Jason D.; Eteleeb, Abdallah; Sauerbeck, Andrew D.; Reitz, Sydney J.; Arhzaouy, Khalid; Ikenaga, Chiseko; Yuede, Carla M.; Pittman, Sara K.; Wang, Feng; Li, Shan; et al. (Cell Reports, 2021)
The pathogenic mechanism by which dominant mutations in VCP cause multisystem proteinopathy (MSP), a rare neurodegenerative disease that presents as fronto-temporal lobar degeneration with TDP-43 inclusions (FTLD-TDP), remains unclear. To explore this, we inactivate VCP in murine postnatal forebrain neurons (VCP conditional knockout [cKO]). VCP cKO mice have cortical brain atrophy, neuronal loss, autophago-lysosomal dysfunction, and TDP-43 inclusions resembling FTLD-TDP pathology. Conditional expression of a single disease-associated mutation, VCP-R155C, in a VCP null background similarly recapitulates features of VCP inactivation and FTLD-TDP, suggesting that this MSP mutation is hypomorphic. Comparison of transcriptomic and proteomic datasets from genetically defined patients with FTLD-TDP reveal that progranulin deficiency and VCP insufficiency result in similar profiles. These data identify a loss of VCP-dependent functions as a mediator of FTLD-TDP and reveal an unexpected biochemical similarity with progranulin deficiency.
CRIS-Team Scopus Importer:2021-07-30
Keywords: autophagy; FTD; FTLD; multisystem proteinopathy; neurodegeneration; progranulin; TDP-43; VCP

New aspects of myofibrillar myopathies - Kley, Rudolf A.; Olive, Montse; Schröder, Rolf (Current Opinion in Neurology, 2016)
Myofibrillar myopathies (MFMs) are hereditary muscle disorders characterized by distinct histopathological features. This review provides an overview of recent research with respect to new disease genes, clinical phenotypes, insights into pathomechanisms and therapeutic strategies.Beyond the known disease genes DES, FLNC, MYOT, CRYAB, ZASP, BAG3, FHL1 and TTN, mutations in PLEC, ACTA1, HSPB8 and DNAJB6 have also been associated with a MFM phenotype. Proteomic analysis revealed new information about the composition of protein aggregates in myotilinopathy and identified a new diagnostic marker. New animal models mirror central aspects of MFM pathology and novel therapeutic strategies for treatment of MFM were evaluated in cell and animal models.MFMs are an expanding and numerically significant group of protein aggregate diseases with marked clinical and genetic heterogeneity. Though no specific therapy is currently available, the generation of patient-mimicking cell and animal models now paves the way for the preclinical evaluation of novel therapeutic strategies.
EVALuna2:7342

New insights into the protein aggregation pathology in myotilinopathy by combined proteomic and immunolocalization analyses - Maerkens, A.; Olive, Montse; Schreiner, A.; Feldkirchner, S.; Schessl, J.; Uszkoreit, Julian; Barkovits, K.; Guettsches, A. K.; Theis, V.; Eisenacher, Martin; Tegenthoff, M.; Goldfarb, L. G.; et al. (Acta Neuropathologica Communications, 2016)
Myofibrillar myopathies are characterized by progressive muscle weakness and impressive abnormal protein aggregation in muscle fibers. In about 10 % of patients, the disease is caused by mutations in the MYOT gene encoding myotilin. The aim of our study was to decipher the composition of protein deposits in myotilinopathy to get new information about aggregate pathology.Skeletal muscle samples from 15 myotilinopathy patients were included in the study. Aggregate and control samples were collected from muscle sections by laser microdissection and subsequently analyzed by a highly sensitive proteomic approach that enables a relative protein quantification. In total 1002 different proteins were detected. Seventy-six proteins showed a significant over-representation in aggregate samples including 66 newly identified aggregate proteins. Z-disc-associated proteins were the most abundant aggregate components, followed by sarcolemmal and extracellular matrix proteins, proteins involved in protein quality control and degradation, and proteins with a function in actin dynamics or cytoskeletal transport. Forty over-represented proteins were evaluated by immunolocalization studies. These analyses validated our mass spectrometric data and revealed different regions of protein accumulation in abnormal muscle fibers. Comparison of data from our proteomic analysis in myotilinopathy with findings in other myofibrillar myopathy subtypes indicates a characteristic basic pattern of aggregate composition and resulted in identification of a highly sensitive and specific diagnostic marker for myotilinopathy.Our findings i) indicate that main protein components of aggregates belong to a network of interacting proteins, ii) provide new insights into the complex regulation of protein degradation in myotilinopathy that may be relevant for new treatment strategies, iii) imply a combination of a toxic gain-of-function leading to myotilin-positive protein aggregates and a loss-of-function caused by a shift in subcellular distribution with a deficiency of myotilin at Z-discs that impairs the integrity of myofibrils, and iv) demonstrate that proteomic analysis can be helpful in differential diagnosis of protein aggregate myopathies.
EVALuna2:7388

Perivascular hemosiderin deposits in human skeletal muscle tissue - Delbridge, Claire; Türk, Matthias; Agaimy, Abbas; Winterholler, Martin; Schröder, Rolf (Neuromuscular Disorders, 2018)
EVALuna2:34586

Plectin-related scapuloperoneal myopathy with treatment-responsive myasthenic syndrome - Argente-Escrig, H.; Schultheis, D.; Kamm, L.; Schowalter, M.; Thiel, C.; Türk, M.; Clemen, C. S.; Muelas, N.; Castañón, M. J.; Wiche, G.; Herrmann, H.; Vilchez, J. J.; et al. (Neuropathology and Applied Neurobiology, 2020)
CRIS-Team Scopus Importer:2020-08-28

Preaged remodeling of myofibrillar cytoarchitecture in skeletal muscle expressing R349P mutant desmin - Diermeier, Stefanie; Buttgereit, Andreas; Schürmann, Sebastian; Winter, Lilli; Xu, Hongyang; Murphy, Robyn M.; Clemen, Christoph S.; Schröder, Rolf; Friedrich, Oliver (Neurobiology of Aging, 2017)
The majority of hereditary and acquired myopathies are clinically characterized by progressive muscle weakness. We hypothesized that ongoing derangement of skeletal muscle cytoarchitecture at the single fiber level may precede and be responsible for the progressive muscle weakness. Here, we analyzed the effects of aging in wild-type (wt) and heterozygous (het) and homozygous (hom) R349P desmin knock-in mice. The latter harbor the ortholog of the most frequently encountered human R350P desmin missense mutation. We quantitatively analyzed the subcellular cytoarchitecture of fast- and slow-twitch muscles from young, intermediate, and aged wt as well as desminopathy mice. We recorded multiphoton second harmonic generation and nuclear fluorescence signals in single muscle fibers to compare aging-related effects in all genotypes. The analysis of wt mice revealed that the myofibrillar cytoarchitecture remained stable with aging in fast-twitch muscles, whereas slow-twitch muscle fibers displayed structural derangements during aging. In contrast, the myofibrillar cytoarchitecture and nuclear density were severely compromised in fast- and slow-twitch muscle fibers of hom R349P desmin mice at all ages. Het mice only showed a clear degradation in their fiber structure in fast-twitch muscles from the adult to the presenescent age bin. Our study documents distinct signs of normal and R349P mutant desmin-related remodeling of the 3D myofibrillar architecture during aging, which provides a structural basis for the progressive muscle weakness.
EVALuna2:7375

Sarcomeric pathology induced by homozygous expression of the myofibrillar myopathy - associated p.W2711X filamin C mutant - Schuld, J.; Orfanos, Z.; Chevessier, Frederic; Unger, A.; Kirfel, G.; Van Der Ven, P.; Linke, W.; Clemen, C.; Fuerst, D.; Schröder, Rolf (NEUROMUSCULAR DISORDERS, 2019)
CRIS-Team WoS Importer:2019-10-11

Severe protein aggregate myopathy in a knockout mouse model points to an essential role of cofilin2 in sarcomeric actin exchange and muscle maintenance - Gurniak, Christine B.; Chevessier, Frederic; Jokwitz, Melanie; Joensson, Friederike; Perlas, Emerald; Richter, Hendrik; Matern, Gabi; Boyl, Pietro Pilo; Chaponnier, Christine; Fuerst, Dieter; Schröder, Rolf; Witke, Walter (European Journal of Cell Biology, 2014)
Mutations in the human actin depolymerizing factor cofilin2 result in an autosomal dominant form of nemaline myopathy. Here, we report on the targeted ablation of murine cofilin2, which leads to a severe skeletal muscle specific phenotype within the first two weeks after birth. Apart from skeletal muscle, cofilin2 is also expressed in heart and CNS, however the pathology was restricted to skeletal muscle. The two close family members of cofilin2 - ADF and cofilin1 - were co-expressed in muscle, but unable to compensate for the loss of cofilin2. While primary myofibril assembly and muscle development were unaffected in cofilin2 mutant mice, progressive muscle degeneration was observed between postnatal days 3 and 7. Muscle pathology was characterized by sarcoplasmic protein aggregates, fiber size disproportion, mitochondrial abnormalities and internal nuclei. The observed muscle pathology differed from nemaline myopathy, but showed combined features of actin-associated myopathy and myofibrillar myopathy. In cofilin2 mutant mice, the postnatal expression pattern and turnover of sarcomeric ?-actin isoforms were altered. Levels of smooth muscle ?-actin were increased and remained high in developing muscles, suggesting that cofilin2 plays a crucial role during the exchange of ?-actin isoforms during the early postnatal remodeling of the sarcomere.
EVALuna2:7241

Stroke in Duchenne Muscular Dystrophy: A Retrospective Longitudinal Study in 54 Patients - Winterholler, Martin; Hollaender, Christian; Kerling, Frank; Weber, Irina; Dittrich, Sven; Türk, Matthias; Schröder, Rolf (Stroke, 2016)
Duchenne muscular dystrophy (DMD) is the most frequent skeletal muscle myopathy. Nearly all patients develop cardiomyopathy in their second decade of life. The purpose of this study was to evaluate the frequency, cause, and outcome of stroke in a German cohort of patients with DMD.Retrospective analysis of medical records of 54 DMD patients, who lived in a regional facility for handicapped people (Wichernhaus Altdorf, Germany) between 1963 and 2013.Fifty-four DMD patients were followed up for 7.4 years on average. Mean age at admission and discharge from the long-term care facility or death were 11.4 and 18.8 years, respectively. Covering a total observation period of 400 patient-years, we identified 4 DMD patients with juvenile arterial ischemic strokes. Off-label systemic thrombolysis in 2 patients resulted in a nearly complete regression of stroke-related symptoms, but 1 patient died of septic pneumonia and cardiac failure 24 days after thrombolysis therapy. In the other 2 patients, who had their ischemic strokes in 1994 and 1998, severe infarction-related symptoms persisted, and 1 patient died 13 days later. DMD-associated cardiomyopathy without evidence of atrial fibrillation was the only risk factor for ischemic stroke in all patients.This study indicates an increased risk for ischemic strokes in DMD patients. Regular cardiological assessment of all DMD patients is mandatory to evaluate the individual risk profile for cardioembolic events and to adapt therapeutic strategies.
EVALuna2:7328

Structure-related force deficit predicted by quantitative multiphoton microscopy of single skeletal muscle fibers from an animal model of human desminopathy - Diermeier, Stefanie; Buttgereit, Andreas; Winter, Lilli; Clemen, C. S.; Schröder, Rolf; Friedrich, Oliver (Wiley-Blackwell, 2015)

Sudden cardiac death, arrhythmogenic cardiomyopathy and intercalated disc pathology due to reduced filamin C protein levels: a matter of life and death - Holtzhausen, Christian; Heil, Lorena; Klingel, Karin; Fox, Henrik; Gummert, Jan; Gärtner, Anna; Schmidt, Andreas; Krüger, Marcus; Kirfel, Gregor; Van Der Ven, Peter F.M.; Milting, Hendrik; Clemen, Christoph S.; et al. (Human Molecular Genetics, 2025)
Mutations in the human FLNC gene encoding filamin C (FLNc) cause a broad spectrum of sporadic and familial cardiomyopathies and myopathies. We report on the genetic, clinical, morphological and biochemical findings in a German family harboring an FLNC variant that leads to severe cardiac disease comprising sudden cardiac death and arrhythmogenic cardiomyopathy. Genetic analysis identified a novel heterozygous FLNC variant in exon 16 (NM_001458.4:c.2495_2498delAGTA, het; p.K832TfsX45) in i) the index patient suffering from dilated cardiomyopathy necessitating heart transplantation, ii) a son, who died from sudden cardiac death, iii) a second son, who survived an episode of sudden cardiac arrest and iv) a third son affected by isolated skeletal muscle myopathy. FLNc protein levels were markedly reduced in cardiac tissue obtained from the index patient, implying that the p.K832TfsX45 FLNc variant most probably caused nonsense-mediated decay of the corresponding mRNA. Morphological analysis of the diseased cardiac tissue revealed extensive fibrotic remodeling, and marked degenerative changes of the contractile apparatus of cardiomyocytes and severe structural alterations of intercalated discs. Connexin-43 signal intensity at intercalated discs was diminished and FLNc labelling of myofibrils was attenuated or even absent. Proteome analyses demonstrated complex alterations of extracellular matrix and intercalated disc proteins. Our findings demonstrate that this novel, truncating FLNC mutation likely leads to haploinsufficiency, thereby causing a deleterious sequence of degenerative changes of cardiac tissue with extensive fibrotic remodeling and intercalated disc pathology as the structural basis for FLNC-related cardiomyopathy with life-threatening cardiac arrhythmias.
CRIS-Team Scopus Importer:2025-04-18
Keywords: arrhythmogenic cardiomyopathy; filamin C/FLNC mutation; intercalated disc; proteome analysis; sudden cardiac death

The desmin mutation R349P increases contractility and fragility of stem cell-generated muscle micro-tissues - Spörrer, Marina; Kah, Delf-Thorge Eric; Gerum, Richard; Reischl, Barbara; Huraskin, Danyil; Dessalles, Claire A.; Schneider, Werner; Goldmann, Wolfgang; Herrmann, Harald; Thievessen, Ingo; Clemen, Christoph S.; Friedrich, Oliver; et al. (Neuropathology and Applied Neurobiology, 2021)
Aims: Desminopathies comprise hereditary myopathies and cardiomyopathies caused by mutations in the intermediate filament protein desmin that lead to severe and often lethal degeneration of striated muscle tissue. Animal and single cell studies hinted that this degeneration process is associated with massive ultrastructural defects correlating with increased susceptibility of the muscle to acute mechanical stress. The underlying mechanism of mechanical susceptibility, and how muscle degeneration develops over time, however, has remained elusive. Methods: Here, we investigated the effect of a desmin mutation on the formation, differentiation, and contractile function of in vitro-engineered three-dimensional micro-tissues grown from muscle stem cells (satellite cells) isolated from heterozygous R349P desmin knock-in mice. Results: Micro-tissues grown from desmin-mutated cells exhibited spontaneous unsynchronised contractions, higher contractile forces in response to electrical stimulation, and faster force recovery compared with tissues grown from wild-type cells. Within 1 week of culture, the majority of R349P desmin-mutated tissues disintegrated, whereas wild-type tissues remained intact over at least three weeks. Moreover, under tetanic stimulation lasting less than 5 s, desmin-mutated tissues partially or completely ruptured, whereas wild-type tissues did not display signs of damage. Conclusions: Our results demonstrate that the progressive degeneration of desmin-mutated micro-tissues is closely linked to extracellular matrix fibre breakage associated with increased contractile forces and unevenly distributed tensile stress. This suggests that the age-related degeneration of skeletal and cardiac muscle in patients suffering from desminopathies may be similarly exacerbated by mechanical damage from high-intensity muscle contractions. We conclude that micro-tissues may provide a valuable tool for studying the organization of myocytes and the pathogenic mechanisms of myopathies.
CRIS-Team Scopus Importer:2021-12-17
Keywords: desmin; desminopathy; micro-tissue; skeletal muscle physiology; tissue engineering

The deubiquitinase USP5 prevents accumulation of protein aggregates in cardiomyocytes - Eibach, Yvonne; Kreher, Silke; Poetsch, Mareike S.; Kho, Ay Lin; Gaertner, Ulrich; Clemen, Christoph S.; Schröder, Rolf; Guo, Kai; Milting, Hendrik; Meder, Benjamin; Potente, Michael; Richter, Manfred; et al. (Science Advances, 2025)
Protein homeostasis is crucial for maintaining cardiomyocyte (CM) function. Disruption of proteostasis results in accumulation of protein aggregates causing cardiac pathologies such as hypertrophy, dilated cardiomyopathy (DCM), and heart failure. Here, we identify ubiquitin-specific peptidase 5 (USP5) as a critical determinant of protein quality control (PQC) in CM. CM-specific loss of mUsp5 leads to the accumulation of polyubiquitin chains and protein aggregates, cardiac remodeling, and eventually DCM. USP5 interacts with key components of the proteostasis machinery, including PSMD14, and the absence of USP5 increases activity of the ubiquitin-proteasome system and autophagic flux in CMs. Cardiac-specific hUSP5 overexpression reduces pathological remodeling in pressure-overloaded mouse hearts and attenuates protein aggregate formation in titinopathy and desminopathy models. Since CMs from humans with end-stage DCM show lower USP5 levels and display accumulation of ubiquitinated protein aggregates, we hypothesize that therapeutically increased USP5 activity may reduce protein aggregates during DCM. Our findings demonstrate that USP5 is essential for ubiquitin turnover and proteostasis in mature CMs.
CRIS-Team Scopus Importer:2025-02-14

The heterozygous R155C VCP mutation: Toxic in humans! Harmless in mice? - Clemen, Christoph S.; Winter, Lilli; Strucksberg, Karl-Heinz; Berwanger, Carolin; Türk, Matthias; Kornblum, Cornelia; Florin, Alexandra; Aguilar-Pimentel, Juan Antonio; Amarie, Oana Veronica; Becker, Lore; Garrett, Lillian; Hans, Wolfgang; et al. (Biochemical and Biophysical Research Communications, 2018)
Heterozygous missense mutations in the human VCP gene cause inclusion body myopathy associated with Paget disease of bone and fronto-temporal dementia (IBMPFD) and amyotrophic lateral sclerosis (ALS). The exact molecular mechanisms by which VCP mutations cause disease manifestation in different tissues are incompletely understood. In the present study, we report the comprehensive analysis of a newly generated R155C VCP knock-in mouse model, which expresses the ortholog of the second most frequently occurring human pathogenic VCP mutation. Heterozygous R155C VCP knock-in mice showed decreased plasma lactate, serum albumin and total protein concentrations, platelet numbers, and liver to body weight ratios, and increased oxygen consumption and CD8+/Ly6C + T-cell fractions, but none of the typical human IBMPFD or ALS pathologies. Breeding of heterozygous mice did not yield in the generation of homozygous R155C VCP knock-in animals. Immunoblotting showed identical total VCP protein levels in human IBMPFD and murine R155C VCP knock-in tissues as compared to wild-type controls. However, while in human IBMPFD skeletal muscle tissue 70% of the total VCP mRNA was derived from the mutant allele, in R155C VCP knock-in mice only 5% and 7% mutant mRNA were detected in skeletal muscle and brain tissue, respectively. The lack of any obvious IBMPFD or ALS pathology could thus be a consequence of the very low expression of mutant VCP. We conclude that the increased and decreased fractions of the R155C mutant VCP mRNA in man and mice, respectively, are due to missense mutation-induced, divergent alterations in the biological half-life of the human and murine mutant mRNAs. Furthermore, our work suggests that therapy approaches lowering the expression of the mutant VCP mRNA below a critical threshold may ameliorate the intrinsic disease pathology.
EVALuna2:36583

The MyoRobot technology discloses a premature biomechanical decay of skeletal muscle fiber bundles derived from R349P desminopathy mice - Haug, Michael; Meyer, Charlotte; Reischl, Barbara; Prölß, Gerhard; Vetter, Karoline; Iberl, Julian; Nübler, Stefanie; Schürmann, Sebastian; Rupitsch, Stefan; Heckel, Michael; Pöschel, Thorsten; Winter, Lilli; et al. (Scientific Reports, 2019)
Mutations in the Des gene coding for the muscle-specific intermediate filament protein desmin lead to myopathies and cardiomyopathies. We previously generated a R349P desmin knock-in mouse strain as a patient-mimicking model for the corresponding most frequent human desmin mutation R350P. Since nothing is known about the age-dependent changes in the biomechanics of affected muscles, we investigated the passive and active biomechanics of small fiber bundles from young (17–23 wks), adult (25–45 wks) and aged (>60 wks) heterozygous and homozygous R349P desmin knock-in mice in comparison to wild-type littermates. We used a novel automated biomechatronics platform, the MyoRobot, to perform coherent quantitative recordings of passive (resting length-tension curves, visco-elasticity) and active (caffeine-induced force transients, pCa-force, ‘slack-tests’) parameters to determine age-dependent effects of the R349P desmin mutation in slow-twitch soleus and fast-twitch extensor digitorum longus small fiber bundles. We demonstrate that active force properties are not affected by this mutation while passive steady-state elasticity is vastly altered in R349P desmin fiber bundles compatible with a pre-aged phenotype exhibiting stiffer muscle preparations. Visco-elasticity on the other hand, was not altered. Our study represents the first systematic age-related characterization of small muscle fiber bundle preparation biomechanics in conjunction with inherited desminopathy.
CRIS-Team Scopus Importer:2019-08-02

The toxic effect of R350P mutant desmin in striated muscle of man and mouse. - Clemen, Christoph; Stöckigt, Florian; Strucksberg, Karl-Heinz; Chevessier, Frederic; Winter, Lilli; Schütz, Johanna; Bauer, Ralf; Thorweihe, José-Manuel; Wenzel, Daniela; Schlötzer-Schrehardt, Ursula; Rasche, Volker; Krsmanovic, Pavle; et al. (Acta Neuropathologica, 2015)
Mutations of the human desmin gene on chromosome 2q35 cause autosomal dominant, autosomal recessive and sporadic forms of protein aggregation myopathies and cardiomyopathies. We generated R349P desmin knock-in mice, which harbor the ortholog of the most frequently occurring human desmin missense mutation R350P. These mice develop age-dependent desmin-positive protein aggregation pathology, skeletal muscle weakness, dilated cardiomyopathy, as well as cardiac arrhythmias and conduction defects. For the first time, we report the expression level and subcellular distribution of mutant versus wild-type desmin in our mouse model as well as in skeletal muscle specimens derived from human R350P desminopathies. Furthermore, we demonstrate that the missense-mutant desmin inflicts changes of the subcellular localization and turnover of desmin itself and of direct desmin-binding partners. Our findings unveil a novel principle of pathogenesis, in which not the presence of protein aggregates, but disruption of the extrasarcomeric intermediate filament network leads to increased mechanical vulnerability of muscle fibers. These structural defects elicited at the myofiber level finally impact the entire organ and subsequently cause myopathy and cardiomyopathy.
Keywords: Desminopathy; R350P desmin missense mutation; Desmin knock-in mouse; Mouse model; Mutant desmin; Intermediate filament; Extrasarcomeric intermediate filament network; Mechanical vulnerability; Protein aggregation myopathy; Skeletal muscle weakness; Protein aggregation cardiomyopathy; Cardiac arrhythmia; Cardiac conduction defect

Translocation of molecular chaperones to the titin springs is common in skeletal myopathy patients and affects sarcomere function - Unger, Andreas; Beckendorf, Lisa; Boehme, Pierre; Kley, Rudolf; Von Frieling-Salewsky, Marion; Lochmueller, Hanns; Schröder, Rolf; Fuerst, Dieter O.; Vorgerd, Matthias; Linke, Wolfgang A. (Acta Neuropathologica Communications, 2017)
Myopathies encompass a wide variety of acquired and hereditary disorders. The pathomechanisms include structural and functional changes affecting, e.g., myofiber metabolism and contractile properties. In this study, we observed increased passive tension (PT) of skinned myofibers from patients with myofibrillar myopathy (MFM) caused by FLNC mutations (MFM-filaminopathy) and limb-girdle muscular dystrophy type-2A due to CAPN3 mutations (LGMD2A), compared to healthy control myofibers. Because the giant protein titin determines myofiber PT, we measured its molecular size and the titin-to-myosin ratio, but found no differences between myopathies and controls. All-titin phosphorylation and site-specific phosphorylation in the PEVK region were reduced in myopathy, which would be predicted to lower PT. Electron microscopy revealed extensive ultrastructural changes in myofibers of various hereditary myopathies and also suggested massive binding of proteins to the sarcomeric I-band region, presumably heat shock proteins (HSPs), which can translocate to elastic titin under stress conditions. Correlative immunofluorescence and immunoelectron microscopy showed that two small HSPs (HSP27 and ?B-crystallin) and the ATP-dependent chaperone HSP90 translocated to the titin springs in myopathy. The small HSPs, but not HSP90, were upregulated in myopathic versus control muscles. The titin-binding pattern of chaperones was regularly observed in Duchenne muscular dystrophy (DMD), LGMD2A, MFM-filaminopathy, MFM-myotilinopathy, titinopathy, and inclusion body myopathy due to mutations in valosin-containing protein, but not in acquired sporadic inclusion body myositis. The three HSPs also associated with elastic titin in mouse models of DMD and MFM-filaminopathy. Mechanical measurements on skinned human myofibers incubated with exogenous small HSPs suggested that the elevated PT seen in myopathy is caused, in part, by chaperone-binding to the titin springs. Whereas this interaction may be protective in that it prevents sarcomeric protein aggregation, it also has detrimental effects on sarcomere function. Thus, we identified a novel pathological phenomenon common to many hereditary muscle disorders, which involves sarcomeric alterations.
EVALuna2:7376

Treadmill exercise intervention improves gait and postural control in alpha-synuclein mouse models without inducing cerebral autophagy - Minakaki, Georgia; Canneva, Fabio; Chevessier, Frederic; Bode, Frederik; Menges, Stefanie; Timotius, Ivanna; Kalinichenko, Liubov; Meixner, Holger; Müller, Christian P.; Eskofier, Björn; Casadei, Nicolas; Riess, Olaf; et al. (Behavioural Brain Research, 2019)
Gait and postural control dysfunction are prototypical symptoms compromising quality of life for patients with Parkinson’s disease (PD). Hallmarks of cellular pathology are dopaminergic degeneration and accumulation of the cytosolic protein alpha-synuclein, linked to impaired autophagy-lysosome pathway (ALP) clearance. Physical exercise improves gait in PD patients and motor function in rodent lesion models. Moreover, exercise is considered neuroprotective and ALP induction has been reported, e.g. in human skeletal muscle, rodent peripheral and cerebral tissues. A combined analysis of how distinct exercise paradigms affect motor and central biochemical aspects of PD could maximize benefits for patients. Here we examine the effect of 4 weeks treadmill exercise intervention in 7-8 month non-lesioned mice on a) distinct gait categories, b) ALP activity, c) dopaminergic and alpha-synuclein homeostasis. The study includes wild type, alpha-synuclein knockout, and mice exclusively expressing human alpha-synuclein. Parameters of gait regularity and stability, activity, and dynamic postural control during unforced walk, were assessed by an automated system (CatWalk XT). At baseline, alpha-synuclein mouse models exhibited irregular and less active gait, with impaired dynamic postural control, compared to wild type mice. Treadmill exercise particularly improved speed and stride length, while increasing dual diagonal versus three-paw body support in both the alpha-synuclein knockout and transgenic mice. Biochemical analyses showed higher striatal tyrosine hydroxylase immuno-reactivity and reduced higher-order alpha-synuclein species in the cerebral cortex. However, no significant cerebral ALP induction was measured. In summary, treadmill exercise improved gait activity and postural stability, and promoted dopaminergic and alpha-synuclein homeostasis, without robustly inducing cerebral ALP.<br
Keywords: alpha-synuclein; autophagy; instrumented gait analysis; mouse gait pattern; Parkinson´s disease; treadmill exercise

Treatment of keratinocytes with 4-phenylbutyrate in epidermolysis bullosa: Lessons for therapies in keratin disorders - Spörrer, Marina; Prochnicki, Ania; Tölle, Regine C.; Nyström, Alexander; Esser, Philipp R.; Homberg, Melanie; Athanasiou, Ioannis; Zingkou, Eleni; Schilling, Achim; Gerum, Richard; Thievessen, Ingo; Winter, Lilli; et al. (EBioMedicine, 2019)
Background: Missense mutations in keratin 5 and 14 genes cause the severe skin fragility disorder epidermolysis bullosa simplex (EBS)by collapsing of the keratin cytoskeleton into cytoplasmic protein aggregates. Despite intense efforts, no molecular therapies are available, mostly due to the complex phenotype of EBS, comprising cell fragility, diminished adhesion, skin inflammation and itch. Methods: We extensively characterized KRT5 and KRT14 mutant keratinocytes from patients with severe generalized EBS following exposure to the chemical chaperone 4-phenylbutyrate (4-PBA). Findings: 4-PBA diminished keratin aggregates within EBS cells and ameliorated their inflammatory phenotype. Chemoproteomics of 4-PBA-treated and untreated EBS cells revealed reduced IL1β expression- but also showed activation of Wnt/β-catenin and NF-kB pathways. The abundance of extracellular matrix and cytoskeletal proteins was significantly altered, coinciding with diminished keratinocyte adhesion and migration in a 4-PBA dose-dependent manner. Interpretation: Together, our study reveals a complex interplay of benefits and disadvantages that challenge the use of 4-PBA in skin fragility disorders.
CRIS-Team Scopus Importer:2019-05-17
Keywords: 4-PBA; Epidermolysis bullosa; Keratinocyte; Keratins; Skin blistering

VCP and PSMF1: Antagonistic regulators of proteasome activity - Clemen, Christoph S.; Marko, Marija; Strucksberg, Karl-Heinz; Behrens, Juliane; Wittig, Ilka; Gaertner, Linda; Winter, Lilli; Chevessier, Frederic; Matthias, Jan; Türk, Matthias; Tangavelou, Karthikeyan; Schütz, Johanna; et al. (Biochemical and Biophysical Research Communications, 2015)
Protein turnover and quality control by the proteasome is of paramount importance for cell homeostasis. Dysfunction of the proteasome is associated with aging processes and human diseases such as neurodegeneration, cardiomyopathy, and cancer. The regulation, i.e. activation and inhibition of this fundamentally important protein degradation system, is still widely unexplored. We demonstrate here that the evolutionarily highly conserved type II triple-A ATPase VCP and the proteasome inhibitor PSMF1/PI31 interact directly, and antagonistically regulate proteasomal activity. Our data provide novel insights into the regulation of proteasomal activity.
EVALuna2:7290

VCP-related multisystem proteinopathy presenting as early-onset Parkinson disease - Regensburger, Martin; Türk, Matthias; Pagenstecher, Axel; Schröder, Rolf; Winkler, Jürgen (Neurology, 2017)
EVALuna2:7395